Characteristics Associated with Motivation to Stop Substance Use and Improve Skin and Needle Hygiene among Hospitalized Patients who Inject Drugs. Issue 1 (December 2022) - Kimmel, Simeon D.; Phillips, Kristina T.; Anderson, Bradley J.; Stein, Michael D.
Background : Hospitalizations for people who inject drugs (PWID) are opportunities to address substance use. However, little is known about hospitalized PWIDs' motivation to stop substance use or improve skin and needle hygiene, common means for reducing injection sequelae. Methods: We used baseline data from a randomized controlled trial of a behavioral intervention to improve skin and needle hygiene among 252 hospitalized PWID between January 2014 and June 2018. We examined motivation (scale 1-10) to stop substance use, use new needles, and clean skin and used multiple linear regression models to evaluate characteristics associated with these outcomes. Results: PWID were recruited during injection-related (154, 61.1%) and non-injection-related hospitalizations (98, 38.9%). Motivation to stop substance use was 7.11 ( SD = 2.67), use new needles was 7.8 ( SD  = 1.9), and clean skin was 6.7 ( SD  = 2.3). In adjusted models, experiencing an injection-related hospitalization was not significantly associated ( p  > 0.05) with motivation to stop substance use (β = −0.76, SE  = 0.299), use new needles (β = 0.301, SE  = 0.255), or clean skin (β = 0.476, SE  = 0.323). Number of past-year skin and soft tissue infections was negatively associated with motivation to use new needles (β = −0.109, SE  = 0.049, p  < 0.05) and clean skin (β = −0.131, SE  = 0.062, p  < 0.05). Greater opioid withdrawal was associated with lower motivation to use new needles (β = −0.275, SE  = 0.92, p  < 0.01). Conclusions: Among hospitalized PWID, motivation to stop substance use and improve skin and needle hygiene was moderately high, but injection-related hospitalizations were not associated with greater motivation. Efforts to reduce injection sequelae for all hospitalized PWID are needed.